![image](https://tex.z-dn.net/?f=3x%5E2-bx-2%3D0%5C%5C%5C%5Cx_1%2B6x_2%3D0.%5C%3B+%5Cto+%5C%3B+x_1%3D-6x_2%5C%5C%5C%5CPo%5C%3B+%5C%3B+teoreme%5C%3B+%5C%3B+Vieta%5C%3B+%5C%3B+x_1%5Ccdot+x_2%3D-%5Cfrac%7B2%7D%7B3%7D%2C%5C%3B+%5C%3B+-6x_2%5E2%3D-%5Cfrac%7B2%7D%7B3%7D%5C%5C%5C%5Cx_2%5E2%3D%5Cfrac%7B2%7D%7B18%7D%3D%5Cfrac%7B1%7D%7B9%7D%5C%3B+%5C%3B+%5Cto+%5C%3B+%5C%3B+x_2%5E%7B%281%29%7D%3D+%5Cfrac%7B1%7D%7B3%7D%2C%5C%3B+%5C%3B+x_1%5E%7B%281%29%7D%3D-6%5Ccdot+%5Cfrac%7B1%7D%7B3%7D%3D-2%5C%5C%5C%5Cx_2%5E%7B%282%29%7D%3D-%5Cfrac%7B1%7D%7B3%7D%2C%5C%3B+x_1%5E%7B%282%29%7D%3D-6%5Ccdot+%28-%5Cfrac%7B1%7D%7B3%7D%29%3D2%5C%5C%5C%5CPo%5C%3B+%5C%3B+ysloviyu%5C%3B+%5C%3B+x_2%3Ex_1%5C%3B+%5C%3B+%5Cto+%5C%3B+%5C%3B+x_1%3D-2%2Cx_2%3D%5Cfrac%7B1%7D%7B3%7D%5C%5C%5C%5CPo%5C%3B+%5C%3B+teoreme%5C%3B+%5C%3B+Vieta%5C%3B+%5C%3B+x_1%2Bx_2%3D%5Cfrac%7Bb%7D%7B3%7D%2C%5C%3B+%5C%3B+%5Cfrac%7Bb%7D%7B3%7D%3D-2%2B%5Cfrac%7B1%7D%7B3%7D%3D-%5Cfrac%7B5%7D%7B3%7D%2C%5C%3B+b%3D-5%5C%5C%5C%5C3x%5E2%2B5x-2%3D0%0A)
x_1\; \; \to \; \; x_1=-2,x_2=\frac{1}{3}\\\\Po\; \; teoreme\; \; Vieta\; \; x_1+x_2=\frac{b}{3},\; \; \frac{b}{3}=-2+\frac{1}{3}=-\frac{5}{3},\; b=-5\\\\3x^2+5x-2=0
" alt="3x^2-bx-2=0\\\\x_1+6x_2=0.\; \to \; x_1=-6x_2\\\\Po\; \; teoreme\; \; Vieta\; \; x_1\cdot x_2=-\frac{2}{3},\; \; -6x_2^2=-\frac{2}{3}\\\\x_2^2=\frac{2}{18}=\frac{1}{9}\; \; \to \; \; x_2^{(1)}= \frac{1}{3},\; \; x_1^{(1)}=-6\cdot \frac{1}{3}=-2\\\\x_2^{(2)}=-\frac{1}{3},\; x_1^{(2)}=-6\cdot (-\frac{1}{3})=2\\\\Po\; \; ysloviyu\; \; x_2>x_1\; \; \to \; \; x_1=-2,x_2=\frac{1}{3}\\\\Po\; \; teoreme\; \; Vieta\; \; x_1+x_2=\frac{b}{3},\; \; \frac{b}{3}=-2+\frac{1}{3}=-\frac{5}{3},\; b=-5\\\\3x^2+5x-2=0
" align="absmiddle" class="latex-formula">